The conversion code : capture internet leads, create quality appointments, close more sales - Smith, Chris, 1979- (Wiley, 2016)
"The business world is moving away from "belly to belly" interactions and traditional advertising. The Conversion Code is a step-by-step blueprint for capturing Internet leads, converting them into appointments and closing prospects into sales. It will teach readers to generate thousands of leads from social media and turn those into closed sales. Much of the sales and marketing advice of yesterday does not apply today's techsavvy, mobilefirst, social media addicted consumers. Instead, companies are being forced to engage with their prospective customer's first online; using social media, mobile apps, blogs and live chat, before ever meeting in-person. No matter what product the company is selling or what industry the company is in, reading this book will increase volume and quality of Internet leads and closed sales."--